First Principles Study on Electronic and Optical Properties of Quinary Copper-based Sulfides and Selenides Cu2HgGe(S1-xSex)4 - Dinh Khang, Pham; Duy Dat, Vo; Phuc Toan, Dang; Van Tuan, Vu (VNU Journal of Science: Mathematics - Physics, 2021)
Electronic and optical properties of Cu 2 HgGe(S 1-x Se x ) 4 compounds ( x = 0, 0.25, 0.5, 0.75, and 1) were revealed by density functional theory (DFT), in which the Heyd-Scuseria-Ernzerhof hybrid functional was used. Dependence of band gap on the Se constituent in Cu 2 HgGe(S 1-x Se x ) 4 was reported. The substitution of Se element basically cause a slightly lattice expansion and minor change of the band gap. Meanwhile, the overlap of Cu and S/Se states becomes more dense leading to better electron/hole pair separation and inter-band transition of photo-excited electrons. The Cu 2 HgGe(S 0.75 Se 0.25 ) 4 compound was predicted to be very promising absorber due to the low band gap, high absorption rate, and low reflectivity in the incoming light energy range from 0 eV to 2 eV.